73. Identification of Novel Factors Associated with Inappropriate Treatment of Asymptomatic Bacteriuria Treatment in Acute and Long-term Care. (4th December 2021) - Valentine-King, Marissa; Van, John; Hines-Munson, Casey E; Dillon, Laura; Graber, Christopher J; Patel, Payal K; Drekonja, Dimitri M; Lichtenberger, Paola; Shukla, Bhavarth; Kramer, Jennifer; Ramsey, David J; Trautner, Barbara; et al.
Abstract: Background: Inappropriate treatment of asymptomatic bacteriuria (ASB) is a major driver of antibiotic overuse. Demographic and laboratory factors associated with inappropriate antibiotic treatment include older age, pyuria, leukocytosis and dementia. To gain a deeper understanding of inappropriate ASB treatment, we performed an in-depth review of provider documentation capturing a broader range of misleading factors associated with ASB treatment. Methods: We reviewed a random sample of 10 positive urine cultures per month per facility from acute or long-term care wards at eight Veteran's Administration (VA) facilities from 2017-2019 (n=960). Trained chart reviewers classified cultures as UTI or ASB and as treated or untreated. Charts were searched specifically for mention of 8 categories of potentially misleading symptoms that often lead to overtreatment of ASB (e.g. "prior history of UTI") (Figure legend). We also created a 'suspected systemic inflammatory response syndrome (SIRS)' category that included any mention of leukocytosis, tachycardia, tachypnea, subjective or low-grade fever, or hypothermia. Generalized estimating equations logistic regression was used for analysis. Results: Our study included 575 cultures from patients that were primarily white (71%) males (94%) from acute medicine units (75.7%) with a mean age of 76. Twenty-eight percent (n=159) of ASB cases received antibiotics. In addition to the usual known predictors, multiple new misleading symptoms were found to be associated with ASB treatment (Table ). Novel, independent predictors of ASB treatment included behavioral issues, such as falls or fatigue (odds ratio (OR): 1.8; 95% CI: 1.05-3.07), urine characteristics, such as cloudy or odorous urine (OR: 1.41; 95% CI: 1.13-1.75), voiding issues (OR: 1.86; 95% CI: 1.43-2.41), and a single, free text mention of a SIRS criteria (OR: 1.63; 95% CI: 1.16-2.3). P-values extracted from multivariate regression model (ASB-asymptomatic bacteriuria; NS-not significant; SIRS- systemic inflammatory response syndrome). The following signs or symptoms compose each category: abnormal laboratory findings: acute kidney injury, abnormal creatinine, leukocytosis, pyuria/positive urinalysis, hyperglycemia; abnormal vital sign: bradycardia, tachycardia, atrial fibrillation, hypotension, hypertension, hypoxia, tachypnea, subjective fever or low-grade fever, syncope; behavior issues: falls, confusion lethargy, fatigue, weakness; nonspecific signs or symptoms: nonspecific gastrointestinal, genitourinary, neurological symptoms; voiding issues: decreased urine output, urinary retention, urinary incontinence; urine characteristics: change in color, foul smell, cloudy urine, sediment; SIRS: ordinal variable characterizing if 1 or ≥ 2 of the following were documented by the provider: leukocytosis, tachycardia, tachypnea, subjective or low-grade fever, hypothermia. Conclusion: Our in-depth chart review, with attention to misleading symptoms and any documentation of the provider thought process, highlights new factors associated with inappropriate ASB treatment. Patients with even a single SIRS criteria are at risk for unnecessary treatment of ASB; this finding can help design antibiotic stewardship interventions. Disclosures: Barbara Trautner, MD, PhD, Genentech (Consultant, Scientific Research Study Investigator)